THE COMPARATIVE ADVANTAGE OF CATTLE FARMING AND ITS CONTRIBUTION TO DONGGALA REGENCY LIVESTOCK DEVELOPMENT - Mujayin, Yudi; Marsetyo, Marsetyo; Maksum, Haerani; Jauhar, Andi; Suharno, Suharno (AGROLAND The Agricultural Sciences Journal (e-Journal), 2025)
Beef cattle business, especially in Central Sulawesi Province, is people's livestock business that needs to be developed. To support the efforts of the development of livestock business, it is necessary to have a data base on the existence of beef cattle and the potential of its development area, so can be used as a basis in establishing the model of beef cattle business development. This study aims to analyze the Comparative Advantage of Cattle Business and Its Contribution to Livestock Development in Donggala Regency by using time series data for 10 years, starting from 2010 to 2019. The analytical model used in this study is a combination of Location Quotient (LQ) and Growth and Share analysis. The Location Quotient (LQ) technique is used as a guide to find out how much cattle have influenced on regional economic growth, by comparing the production value in the area namely Donggala Regency. The acquisition of the LQ value of cattle in Donggala Regency is 1.03 > 1 which means that the beef cattle business is a basic sector, it can be said that cattle have a comparative advantage because they are able to provide regional markets and markets outside the region from Donggala Regency. Based on the Growth and Share analysis, beef cattle commodities have positive growth where x = 8, with a contribution (positive share) X = 9.8 > 2, and it is stated that the beef cattle business is superior and contributes greatly to the development of livestock in Donggala Regency.